Relationship of stunting with water, sanitation, and hygiene (WASH) practices among children under the age of five: a cross-sectional study in Southern Punjab, Pakistan - Munazza Batool; Javeria Saleem; Rubeena Zakar; Muhammad Salman Butt; Sanaullah Iqbal; Shahroz Haider; Florian Fischer (BMC, 2023)
Abstract Background Reasons for undernutrition are food insufficiency, impaired child care, limited access to healthcare, and maternal lack of health literacy. In addition, there are several environmental factors, such as drinking water quality, poor sanitation, and hygienic practices that can lead to poor nutritional status in children. The present study aimed to compare household-associated risk factors, including water, sanitation, and hygiene (WASH) practices of mothers, with children's stunting under the age of five. Methods A face-to-face cross-sectional survey was conducted with mothers of children under the age of five in the Dera Ghazi Khan district in southern Punjab, Pakistan. World Health Organization criteria for stunting were used to identify the participants. A sociodemographic questionnaire was used to collect information from consented parents/guardians on children's age, feeding, and WASH practices. Pearson's chi-square, simple regression, and hierarchical regression models were applied for data analysis. Results A total of 204 mothers of children of both genders participated in this study. The children's mean (SD) age was 15.67 (± 10.2) months, their weight was 5.44 (± 1.45) kg, their height was 67.69 (± 10.05), and their mid-upper arm circumference was 9.75 (± 1.30) cm. Children's stunting was mild (z-score > -2) at 17.6%, moderate (z-score − 2 to -3) at 16.7%, and severe (z-score < -3) at 65.7% of participants. A simple regression model showed a strong association, r2 = 0.062, p = 0.013, with age as the most significant sociodemographic factor. The hierarchical regression model showed a combined value of r2 = 0.0128, p = 0.027, with hand pump and tank water as the significant source of drinking water that was related to stunting among children. Conclusion Stunting can be associated with several risk factors, including WASH parameters. This study concluded that children aged under five years are susceptible to stunting in southern Punjab, Pakistan. The contamination of hand pumps and tank water resources was found to be the major contributing factor to stunting.